RPA Integration with Identity Management Platforms: A Scalable IAM Orchestration Pattern - Neha Asthana (International Journal of Computational and Experimental Science and Engineering, 2026)
The rapid proliferation of non-human identities across cloud and hybrid environments has exposed significant gaps in conventional identity governance architectures, which were designed primarily around human access patterns and periodic compliance assessment cycles. Integrating robotic process automation with identity governance platforms introduces a scalable orchestration model in which the governance platform serves exclusively as the policy and decision authority while automation agents execute provisioning tasks through a database-mediated communication layer. This separation of policy enforcement from execution responsibility eliminates uncontrolled privilege escalation and enables provisioning across applications that lack native connector support. Continuous behavioral authentication mechanisms, multi-interface communication redundancy, cryptographic audit trail enforcement, and event-driven remediation together form a unified control architecture that extends identity assurance beyond point-in-time verification into the full operational lifecycle. Quantifiable improvements in provisioning speed, compliance accuracy, breach risk reduction, and administrative cost confirm that governance-centric automation delivers measurable security and operational value across regulated enterprise environments.